A multiplex-conventional PCR assay for bovine, ovine, caprine and fish species identification in feedstuffs: Highly sensitive and specific. (April 2015) - Safdar, Muhammad; Junejo, Yasmeen
Abstract: A multiplex PCR assay was developed for rapid and reliable identification of bovine, ovine, caprine and fish species in feedstuffs simultaneously. The method merges the use of bovine, ovine, caprine and fish primers that amplify fragments (ovine; 119 bp, caprine; 142 bp, fish; 224 bp and bovine; 271 bp) of the mitochondrial t.glu gene forward and cyt b reverse, 12S rRNA, 12S rRNA, and ATPase subunit 8 genes respectively, and a universal 18S rRNA primers that amplifies a 99 bp from eukaryotic DNA. To evaluate the effect of heat treatment, a severe sterilization condition (133 °C at 300 kPa for 20 min) was applied. Multiplex analysis of the reference feedstuff samples showed that the detection limit of the assay was 0.01% for each species. Taken together, all data indicated that this multiplex PCR assay was a simple, rapid, sensitive, specific, and cost-effective detection method for bovine, ovine, caprine and fish species in feedstuffs. Highlights: This work describes a Multiplex PCR assay for cow, sheep, goat and fish species detection in one tube. Universal Eukaryotic Primers reveal: DNA degradation, equipment deficiency. Advantages: rapid, cost-effective, reliable, highly sensitive and specific. Application: verification of labeling, normative control, products traceability. Useful for protection of the consumer's rights and for feed products control.